Northern Lights Chase Tours: Experiences from Northern Norway - Bertella, Giovanna (Journal of Northern Studies, 2014)
This study is focused on the development of northern lights chase tourism, a particular type of northern lights tourism consisting in guided tours that have the goal to find good views of the northern lights. The theoretical approach is based on the understanding of the northern lights experience as a visual experience, and on the recognition of the tourism practitioners as the driving force to new product development. The empirical case concerns the recent development of northern lights chase tourism in the Tromsø area, in Northern Norway. The aim of this study is to investigate the tourism practitioners’ understanding of the northern lights chase tourism, with a particular focus on the development of such a form of tourism as a source of positive memorable experiences. The research questions are: How is the northern lights chase tourism experience described by the tourism practitioners involved in its development? What are the recognized potentials, critical factors and challenges in terms of memorability? On the basis of the empirical results, this study indicates actions directed at fully exploiting the identified potentials, and meeting the relative challenges, and considers critically the adopted theoretical approach proposing directions for future research.